Routine post-harvest screening of banana/plantain hybrids: Criteria and methods - Dadzie, B.K.; Orchard, J.E. (1997)
This manual describes the key post-harvest criteria and methods/procedures for routine selection of new Musa hybrids. There are many post-harvest criteria for screening new banana, cooking banana and plantain hybrids, however the major ones include : post-harvest characteristics at harvest, fruit maturation, green-life and shelf-life, fruit ripening quality, sensory quality, cooking or boiling quality, processing quality, mechanical damage, physiological disorders and post-harvest diseases. English version out of print INIBAP / CTA / NRI / FHIA / ODA